Cryoglobulinaemia in Egyptian Patients with Extrahepatic Cutaneous Manifestations of Chronic Hepatitis C Virus Infection - Doaa Salah Hegab; Mohammed Abd El Rahman Sweilam (Dermatology Research and Practice)
Background. Hepatitis C is a global major health problem with extremely variable extrahepatic manifestations. Mixed cryoglobulinaemia (MC) shows a striking association with hepatitis C virus (HCV) infection, and it is sometimes asymptomatic. The skin is a frequently involved target organ in MC. Objective. To investigate the prevalence of cryoglobulinaemia in a sample of Egyptian patients with cutaneous manifestations of chronic HCV infection and to correlate its presence with clinical criteria and liver function tests. Methods. One hundred and eighteen patients with skin manifestations of chronic compensated hepatitis C were included. Venous blood was tested for liver function tests and serum cryoglobulins. Results. Twelve patients (10.169%) were positive for serum cryoglobulins (2 with pruritus, 4 with vasculitic lesions, 3 with livedo reticularis, one with oral lichen, one with chronic urticaria, and another with Schamberg’s disease). Vasculitic lesions and livedo reticularis of the legs showed higher prevalence in cryoglobulin-positive than in cryoglobulin-negative patients. Presence of serum cryoglobulins did not relate to patients’ demographic or laboratory findings. Conclusions. Fortunately, MC is not markedly prevalent among Egyptians with cutaneous lesions of chronic hepatitis C, and cryopositivity was commonly, but not exclusively, detected with cutaneous vasculitis and livedo reticularis. Laboratory testing for cryoglobulins in every HCV patient is advisable for earlier MC detection and management.